Pengembangan Sistem Layanan Administrasi Kependudukan Desa Papasan dengan QR Code sebagai Validasi Dokumen - Nur Cahyo Hendro Wibowo; Albadru Muh Izul Khaq; Siti Nur'aini (Universitas Islam Negeri Walisongo Semarang, 2023)
Papasan Village is located in the Bangsri sub-district, Jepara district. The process of managing mail services in a day serves 20 submissions of letters. This mail service process is still done manually so it takes a relatively long time. Another problem is the potential for document falsification because administrative data reports are not recorded properly, so in this study a population administration service system was developed that utilizes the Quick Response Code (QR Code). System development is carried out using the waterfall method. The system design stage is carried out using Data Flow Diagrams, while the database design is carried out by compiling a Physical Data Model. The QR Code on the letter is scanned through the system to determine the authenticity of the letter. System testing involved 30 respondents consisting of village heads and village residents. The first test using a black box results that the system can run if the data entered is appropriate and the data is not empty. The second test uses the User Acceptance Test (UAT), the total percentage results are 88% or the system is in the very good category. Desa Papasan terletak di kecamatan Bangsri, kabupaten Jepara. Proses pelayanan pengurusan surat dalam sehari melayani 20 pengajuan surat. Proses pelayanan surat ini masih dilakukan secara manual sehingga membutuhkan waktu yang relatif lama. Permasalahan lainnya adalah adanya potensi pemalsuan dokumen karena laporan data administrasi tidak tercatat dengan baik, maka dalam penelitian ini dikembangkan sistem pelayanan administrasi kependudukan yang memanfaatkan Quick Response Code (QR Code). Pengembangan sistem dilakukan dengan menggunakan metode waterfall. Tahap perancangan sistem dilakukan dengan menggunakan Data Flow Diagram, sedangkan perancangan basis data dilakukan dengan menyusun Model Data Fisik. QR Code pada surat dipindai melalui sistem untuk mengetahui keaslian surat. Pengujian sistem melibatkan 30 responden terdiri dari kepala desa dan warga desa. Pengujian pertama menggunakan black box hasilnya sistem dapat berjalan jika data yang dimasukkan sesuai dan data tidak kosong.